Exploring Students’ Acceptance Level of Learning Management System (LMS) as E-learning Platform using Technology Acceptance Model (TAM) at Manado State University - Keith Francis Ratumbuisang; Yosua Fitsgerald Ratumbuisang; Djubir Ruslan Eddy Kembuan; Johan Reimon Batmetan; Merriam Modeong (Technium: Romanian Journal of Applied Sciences and Technology, 2023)
This study aims to identify elements that can project the use of e-learning among Manado State University students through the application of path analysis. This study utilizes the Technology Acceptance Model (TAM) framework as a theoretical foundation that guides in analysing the relationship between external and internal variables. The series of concepts proposed involves six main variables, as shown in Figure 1. The model presents the concept of supporting condition variables as an integrated external element in the Technology Acceptance Model. According to the analysis, AT, BI, FC, PEU ATU impact the desire to utilize LMS, When the endogenous latent variable’s Q-square score is positive, indicating that the endogenous latent variable is predictive. Meanwhile, hypothesis testing revealed that one of the eight submitted hypotheses, H4, was rejected, while the others were approved.